2021
DOI: 10.1111/jfs.12926
|View full text |Cite
|
Sign up to set email alerts
|

Food safety knowledge, hygiene practices, and eating attitudes of academics and university students during the coronavirus (COVID‐19) pandemic in Turkey

Abstract: The purpose of this study is to assess the effect of the coronavirus (COVID‐19) pandemic on food safety knowledge, hygiene practices, and eating attitudes of academics and university students in Turkey. A cross‐sectional survey invitation was emailed to the participants from various academic ranks and departments at chosen universities from different region of country. Academics were requested to forward the invitation email to enrolled students to their classes. Responds were accepted in the period of 45 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
1
3
0
1
Order By: Relevance
“…According to a cross-sectional study conducted on Jouf University students in 2020, the Saudi Ministry of Health’s education program was potent in terms of raising awareness and educating the public in regard to COVID-19 [ 19 ]. Similar results can be found in a 2020 cross-sectional study conducted in Turkey which states that the hygienic practices of academic and student participants have increased during the COVID-19 pandemic [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…According to a cross-sectional study conducted on Jouf University students in 2020, the Saudi Ministry of Health’s education program was potent in terms of raising awareness and educating the public in regard to COVID-19 [ 19 ]. Similar results can be found in a 2020 cross-sectional study conducted in Turkey which states that the hygienic practices of academic and student participants have increased during the COVID-19 pandemic [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…Finally, all consumer handling studies were performed before the coronavirus disease 2019 (COVID-19) pandemic, which is believed to have significantly increased consumer hygiene practices (i.e. hand washing) [ 41 , 42 ] with a potential effect on the cross-contamination model assumptions and reduction in the illness estimates.…”
Section: Resultsmentioning
confidence: 99%
“…While the rate of individuals who know that COVID-19 is a viral infection is 68%, the rate of those who do not take precautions against this factor is 3.8%. While 54.4% of the respondents reported that they had the COVID-19 PCR test, 19.4% of them stated that they were positive. The rate of those who think that the agent is not transmitted through food, but can be transmitted through food packaging, was determined as 39.8%.…”
Section: Materials and Methods: It Consists Of Volunteer Individualsmentioning
confidence: 99%